Membangun jaringan support system sebaya: inisiatif pengembangan kompetensi guru bimbingan dan konseling MTs Kota Malang dalam mengatasi masalah siswa - Khairul Bariyyah; Adi Atmoko; Ella Faridati Zen; Rizka Apriani (Lentera Negeri, 2023)
Guidance and Counseling services in MTs (Islamic Junior High School) are not optimal due to the limited personnel and counseling hours in schools, leading students to seek help from their peers to solve their problems. One of the efforts made to build a positive peer culture is by developing peer counseling services. This program is designed through community service conducted over 6 months. The assistance provided includes (1) Preparation Stage, exploring materials for the peer counselor program as a strategy to handle student problems, (2) Implementation Stage, training to identify the level of social relationships among students through Sociometry to form peer counselors, training for school counselor to develop the peer counselor program, basic listening skill training, appointing a peer counselor team at school, (3) Evaluation and Follow-up Stage, evaluating and following up on the peer counselor program as a strategy to handle student problems. The community service partners are 24 school counselor from MTs in Malang City. The evaluation of the results is conducted by assessing the level of satisfaction of school counselor and the success of establishing the peer counselor program in schools. The instruments used are the Peer Counselor Formation Evaluation Form and the Basic Listening Skill Test for peer counselors. Based on the evaluation results, 75% of MTs in Malang City now have peer counselors. This program has also succeeded in providing support to students in improving their mental health quality and enhancing their communication skills. The sustainability of this program is ensured by holding advanced training related to other student problem-solving skills periodically, according to the needs of students/peer counselors.